Efficient Implementation of Spreadsheet User Application - Repič, Tjaša; Jeromel, Aljaž; Piskar, Sašo; Dolanc, Domen; Lukač, Niko (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
Processing measurement data is fundamental in the field of high-tech instrumentation, where precision, collection, analysis, and visualization of data are of great importance. Extensive amounts of data ought to be displayed and processed to ensure smooth user experience. Tabular displays are therefore common, being more comprehensible for the average user. In this paper we propose a so-lution, envisioned by the company Dewesoft - a spreadsheet editor widget tailored for their data acquisition software DewesoftX, also compatible with separate plugins within the software. Since using commercially widespread tools to do so often results in setbacks when seeking to integrate those within existing software, we’ve de-veloped an application functionally comparable to other solutions while complying with the company’s existing software standards.